ANALISIS KESTABILAN MODEL DINAMIK ALIRAN FLUIDA DUA FASE PADA SUMUR PANAS BUMI - Utomo, Robertus Heri Soelistyo; ., Widowati; Tjahjana, Redemtus Heru; Niswah, L (MATEMATIKA, 2014)
In this paper is discussed about the analysis of the stability of fluid flow dynamical model of two phases on the geothermal wells. The form of the model is non-linear differential equation. To analyze the local stability around the equilibrium point, first, the non linear models of is linearized around the equilibrium point using Taylor series. Further, from linearized model, we find a Jacobian matrix, where all of the real eigen values of the Jacobian matrix are zeros. So that the behviour of the dynamical system obtained around the equilibrium point is stable. Â